THE 21ST CENTURY EDUCATION: A SYSTEMATIC LITERATURE REVIEW OF TRANSFORMING LEARNING METHODS TO FOSTER CRITICAL THINKING SKILLS THROUGH AUGMENTED REALITY IN SCIENCE LEARNING - Kurniawan, Aris; Jumadi, Jumadi; Kuswanto, Heru; Syar, Nur Inayah (JURNAL EDUSCIENCE, 2024)
This study aims to examine the potential of augmented reality in enhancing science learning, with a particular focus on physics learning. It involves a qualitative synthesis of previous research, incorporating both quantitative and qualitative studies, that explores instructional designs using augmented reality in science learning and its effects on students' critical thinking skills. The study analyzes articles published between 2014 and 2023 in the Scopus database, with 46 articles selected for in-depth analysis and synthesis. The findings indicate that integrating augmented reality in science learning can enhance students' thinking skills, particularly critical thinking skills. The use of learning models such as discovery learning, problem-based learning, and inquiry-based learning can make learning more meaningful and increase student engagement in the learning process. No studies have been identified that assess multi-representation skills in science learning through augmented reality. Further research is essential to investigate the specific effects of augmented reality media on students' multi-representation skills.